The Immersive Virtual Reality Lab: Possibilities for Remote Experimental Manipulations of Autonomic Activity on a Large Scale - Juvrud, Joshua; Gredebäck, Gustaf; Åhs, Fredrik; Lerin, Nils; Nyström, Pär; Kastrati, Granit; Rosén, Jörgen (Frontiers in Neuroscience, 2018)
There is a need for large scale remote data collection in a controlled environment, and the in-home availability of virtual reality (VR) and the commercial availability of eye-tracking for VR presents unique and exciting opportunities for researchers. We propose and provide a proof-of-concept assessment of a robust system for large-scale in-home testing using consumer products that combines psychophysiological measures and VR, here referred to as a Virtual Lab. This method is validated by correlating for the first time autonomic responses, skin conductance response (SCR) and pupillary dilation, in response to a spider, a beetle, and a ball using commercially available VR. Participants demonstrated greater SCR and pupillary responses to the spider, and the effect was dependent on the proximity of the stimuli to the participant, with a stronger response when the spider was close to the virtual self. We replicated these effects across two experiments and in separate physical room contexts to mimic variability in home environment. Together these findings demonstrate the utility of pupil dilation as a marker of autonomic arousal and the feasibility to assess this in commercially available VR hardware, and support a robust Virtual Lab tool for massive remote testing.